Illness Perceptions in Thai Patients with Myocardial Infarction: A Cross-Sectional Observational Study - Kritpracha, Charuwan; Lanwong, Tanika; Tinkaew, Phenpitcha; Buatchum, Kornwika; Songwathana, Praneed (Journal of The Royal Thai Army Nurses, 2025)
This research aimed to examine illness perceptions of Thai patients with myocardial infarction. A cross-sectional observational study was conducted with a purposively selected 50 Thai adult patients with myocardial infarction (MI). Data were collected using the Revised Illness Perceptions Questionnaire with the Cronbach’s alpha of 0.86, and open-ended questions, to explore the MI illness perceptions. Quantitative data were analyzed by descriptive statistics and qualitative data were analyzed using content analysis. The results based on illness perceptions revealed that chest pain was the most experienced symptom in the past one month before MI diagnosis (n=41; 82%) and chest pain was perceived as a symptom related to MI (n=37; 74%). The highest score of illness perceptions is the Consequences domain (mean=3.55, SD=0.55), followed by the Cure/Controllability domain (mean=3.36, SD=0.30) and the Treatment Control domain (mean=3.47, SD=0.39). The three most perceived causes of MI were overwork (mean=4.20, SD=.86), diet or eating habits (mean=3.96, SD=1.01), and alcohol (mean=3.70, SD=.86) respectively. Results from open-ended questions provided in-depth content of illness perceptions of Thai patients with myocardial infarction.